2020
DOI: 10.1177/1078155219897129
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pharmacist interventions in a head and neck medical oncology clinic

Abstract: Introduction Head and neck cancers (HNC) are a complex and heterogeneous group of cancers, often necessitating a multidisciplinary approach across the care continuum. Oncology pharmacists are uniquely qualified to play a vital role on a multidisciplinary team and provide specialized care to optimize medication therapy. Methods This was a retrospective chart review evaluating the role of a board-certified oncology pharmacist in the head and neck oncology clinic at an academic, comprehensive cancer center from A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Studies conducted globally have confirmed the benefit of the integration of the OPT as part the MHT within a variety of settings in improving overall patient care. 2252…”
Section: Contributions To Patient Carementioning
confidence: 99%
“…Studies conducted globally have confirmed the benefit of the integration of the OPT as part the MHT within a variety of settings in improving overall patient care. 2252…”
Section: Contributions To Patient Carementioning
confidence: 99%
“…Lau conducted a retrospective chart review, in which patient education was the most performed intervention (58%), followed by ordering new prescriptions or refill requests (49.9%), and provision of supportive care (32.6%). 22 According to the ratings provided by the panellists 454 (78.27%) discrepancies were classified as Significant, 80 (13.79%) were classified as Serious and 46 (7.93%) were classified as Not Significant. Similar to ours, a study was conducted by Knez et al, where an expert panel provided the clinical significance of medication errors.…”
Section: Discussionmentioning
confidence: 99%
“…The total acceptability of pharmacist interventions performed in these situations demonstrates their relevance and signals how the CMM service effectively serves as a valuable screening tool for patients who undergo RITwhich, in itself, poses multiple challenges for health teams. 10,11 CMM is based on a generalist and patient-centered clinical practice, which allows for comprehensive and holistic pharmacotherapy assessments. 13 Therefore, this service allows for the expansion of the team's view of the patient's pharmacotherapeutic needs, which most of the timein the context of oncology and other specialtiesinvolves a limited focus on the condition of their field of work.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, before the administration of this radiopharmaceutical, the role of a multiprofessional team is paramount and can benefit considerably from the presence of a pharmacist. 9,10 In addition, after RIT, most patients with DTC become cancer survivors because this is an indolent type of cancer that presents low mortality, high overall survival rates, and disease-free survival of over 90% in five years. 8,11,12 This causes DTC survivors to demand a long-term follow-up in the post-RIT period.…”
Section: Introductionmentioning
confidence: 99%